Bone marrow transplantation across major genetic barriers - Reisner, Yair; Martelli, M. F. (World Scientific, 2010)
The importance of bone marrow transplantation for patients who do not have a matched sibling donor cannot be overestimated. This subject has always been in the public domain, accentuated by dramatic appeals, from time to time, to search for matched volunteer donors in the public at large. Unfortunately, the availability of such donors is limited, due to the remarkable genetic diversity of humans. Thus, although registries of such volunteers now include more than seven million individuals, we still face the problem of finding a matched donor for about 30 per cent of patients in need. To address.